The prognostic impact of tumor-infiltrating B lymphocytes in patients with solid malignancies: A systematic review and meta-analysis. (January 2023) - Liu, Hao; Li, Zhuoqun; Han, Xuan; Li, Zhujun; Zhao, Yan; Liu, Fenghua; Zhu, Ziyu; Lv, Yi; Liu, Zhijun; Zhang, Nana
Abstract: This study reviewed the prognostic effect of tumor-infiltrating B lymphocytes (TIBLs) on solid malignancies, to determine the potential role of TIBLs in predicting cancer patient's prognosis and their response to immunotherapy. A total of 45 original papers involving 11, 099 individual patients were included in this meta-analysis covering 7 kinds of cancer. The pooled results suggested that high levels of TIBLs were correlated with favorable OS in lung, esophageal, gastric, colorectal, liver, and breast cancer; improved RFS in lung cancer; and improved DFS in gastrointestinal neoplasms. Additionally, TIBLs were significantly correlated with negative lymphatic invasion in gastric cancer, small tumor size in hepatocellular carcinoma, and negative distant metastasis in colorectal cancer. Additionally, TIBLs were reported as a discriminative feature of patients treated with immunotherapy with improved survival. We concluded that TIBLs play a favorable prognostic role among the common solid malignancie, providing theoretical evidence for further prognosis prediction for solid tumors. Highlights: Analyze and review the prognostic value of B cells in solid tumors from different systems. Assess the relationship between tumor-infiltrating B cells and other clinicopathological parameters. Evaluate the potential role of B cells in cancer immunotherapy.